(untitled) (Research, Society and Development, 2022)
Background: COVID-19 is an inflammatory disease caused by SARS-CoV-2, in which the patient can progress to a hypercoagulable state, requiring antithrombotic therapy. Objectives: To describe data from the literature on the use of anticoagulants as a treatment for COVID-19 positive patients and their impact on the oral cavity, the platelet antiaggregants and anticoagulants used to aid in the treatment of the Covid-positive patient, the exams and markers that help the choice of the therapy to be used, as well as observing the treatment and associating it with the risk of oral bleeding. Methodology: A bibliographic survey was carried out from 2012 to 2021 in the BvSalud research base. The keywords “Covid”, “anticoagulants” and “risk factors” and their corresponding words in English “Covid”, “anticoagulants and “risk factors” were used. Results: 128 articles were selected in BvSalud, after reading 68 articles were excluded, leaving 60 articles that met the criteria for literature review. Conclusion: Covid-19 is a pathology that acts on ACE2 receptors, triggering an inflammatory response and activating the coagulation cascade, hematological tests (D-dimer, fibrinogen, ferritin, prothrombin time, interleukin-6 and Protein-C- reactive) can be used to assess the patient’s status. The decision to initiate anticoagulant or antiplatelet therapy should be made after evaluating these markers. Such therapy can exacerbate bleeding resulting from oral trauma at the time of intubation or from preexisting ulcers or ulcers acquired after ICU admission, the installation of ETT requires special care with the patient’s oral hygiene, in view of the greater susceptibility to secondary infections.